Model dan strategi pengembangan ekonomi kreatif pada obyek wisata pantai di Kabupaten Flores Timur - H.J. Fanggidae, Apriana; Neno, Marianus Saldanha (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The creative economy is defined as an economic sector that relies on ideas and human creativity as its main production factor. Ideas and knowledge are the main factors and are supported by the ease and progress of technology and the competence of the workforce. The purpose of the research is to find solutions to real problems such as Analyzing creative economic business development strategies on beach tourism objects in East Flores Regency and Describing creative economic business development models on Beach Tourism Objects in East Flores Regency. Data analysis was conducted using qualitative and quantitative approaches. Based on the results of the SWOT analysis, it can be concluded that the total IFAS value is 2,895 and the total EFAS value is 2,555. This proves that the company is in the position of Cell V in the IE matrix which proves the Average Internal and Medium External conditions. This position indicates that the company is in a developing and stable condition. In this case, the strategy that can be applied is the Defense and Maintenance strategy with opportunities for market penetration and product development.